Exposure of the Instagram Account @hungry.cikarang to Fulfilling the Information Needs of Authentic Indonesian Culinary to Followers - Diana Sari,; Susilowati Dyah K,; Ashur Harmadi,; Didin Mukodim,; Khusnul Khofifah, (International Journal of Scientific Research in Science and Technology, 2024)
Instagram @hungry.cikarang is an account based on information content about culinary delights in Cikarang. This research aims to determine the influence of exposure to social media Instagram @hungry.cikarang on fulfilling the culinary information needs of followers. The research method used is a quantitative method with a survey approach of 100 respondents as a sample. The data obtained were analyzed using validity tests, reliability tests, normality tests, linearity tests, simple linear regression analysis, t tests and coefficient of determination tests. From this research, the results of a simple linear regression equation were obtained, namely Y= 22.737 + 0.623X, which means that the influence of exposure to social media Instagram @hungry.cikarang has a significant positive influence on fulfilling the culinary information needs of followers. Based on the results of the hypothesis test, namely the t test, it shows that there is an influence of exposure to social media Instagram @hungry.cikarang on fulfilling the culinary information needs of followers. Meanwhile, the test result for the R Square coefficient of determination is 0.414. These results explain the ability of the media exposure variable (X) to influence the information needs fulfillment variable (Y), which is 41.4%, while the remaining 58.6% is explained by other factors not included in this research.
Keywords: Exposure Instagram; Fulfilling Information; Followers; Indonesian Culinary